Regurgitação valvar funcional em insuficiência cardíaca congestiva descompensada: monitoração não-invasiva por bioimpedância cardíaca e ecocardiografia e resposta à terapêutica - Campos, Paulo César Gobert Damasceno [UNIFESP] (2009)
Objective: We hypothesized that functional mitral and tricuspid valvular incompetence (MR and TR, respectively) are reversible causes of reduced cardiac output in decompensated heart failure (DF) that accompanies systolic dysfunction in ischemic or nonischemic cardiomyopathy. Background: DF, defined as signs and symptoms of heart failure at rest, is rooted in a salt-avid state transduced by neurohormonal activation secondary to impaired renal perfusion. Functional MR and TR are reversible causes of reduced systemic blood flow. Their impact on cardiac output, thoracic fluid content, cardiac chamber dimensions, and valvular apparatus function can be monitored noninvasively, before and after optimized medical management. Methods: Fourteen male subjects (66 ± 8 years old) with reduced ejection fraction (24 ± 5%) secondary to ischemic (71%) or nonischemic (29%) cardiomyopathy, who developed DF with clinical evidence of mitral (MR) and tricuspid (TR) valvular incompetence, were each assessed by bioimpedance and echocardiography before and 1 week after optimized medical management restored compensated failure. Results: Pharmacologic elimination of DF was accompanied by a reduction in body weight (p<0.01). Hemodynamic improvements included a rise in cardiac index (2.1 to 2.6 L/min/m2; p<0.01) and a reduction in predicted pulmonary artery systolic pressure (58 to 35 mm Hg; p<0.001), thoracic fluid content (39 to 32 kOhm; p<0.001), and systemic vascular resistance (1633 to 1209 dynes/sec/cm5; p<0.001). Improvements in functional MR and TR included reductions in left and right atrial areas (27 to 24 cm and 26 to 23 cm2, respectively; p<0.001), color-flow grading of MR and TR severity (p<0.01), mitral regurgitant volume (105 to 65 mL; p<0.001), and effective MR orifice size (0.8 to 0.6 cm2; p<0.01). Conclusions: In DF, functional MR and TR contribute to reduced cardiac output, increased thoracic fluid content, and systemic vascular resistance, together with enlarged atria and valvular orifice size, which can be improved by medical management. Bioimpedance and echocardiography provide for serial noninvasive assessments of hemodynamic status and valvular function in such cases.